2013
DOI: 10.18632/oncotarget.1397
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum anti-tumor and anti-metastatic DNA vaccine based on p62-encoding vector

Abstract: Autophagy plays an important role in neoplastic transformation of cells and in resistance of cancer cells to radio- and chemotherapy. p62 (SQSTM1) is a key component of autophagic machinery which is also involved in signal transduction. Although recent empirical observations demonstrated that p62 is overexpressed in variety of human tumors, a mechanism of p62 overexpression is not known. Here we report that the transformation of normal human mammary epithelial cells with diverse oncogenes (RAS, PIK3CA and Her2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…osteosarcoma, oral squamous cell carcinoma, cutaneous malignant melanoma, esophageal adenocarcinoma, ovarian, colon, breast and non-small cell lung cancers, and solid tumors Daniels et al, 2013;Ellis et al, 2014;Giatromanolaki et al, 2014;Inoue et al, 2012;Iwadate et al, 2014;Liu et al, 2014a;Luo et al, 2013;Ma et al, 2018;Niklaus et al, 2017;Park et al, 2013;Ruan et al, 2018;Schläfli et al, 2016), and has attracted attention as a potential therapeutic target (Yan et al, 2017;Zhang et al, 2016). An antitumor SQSTM1 DNA vaccine has already been developed and trialed in humans (Gabai et al, 2014;Ponomarenko et al, 2017;Sabbieti et al, 2015;Venanzi et al, 2013); however, SQSTM1 can have both beneficial and deleterious effects depending on the pathological context, as is the case for autophagy itself (Dikic and Elazar, 2018). Then, any hope to develop successful therapeutic strategies in pathologies with SQSTM1 alterations needs to keep in mind the complexity of the SQSTM1 signaling network and how it is affected in each particular disease situation: its tight posttranslational regulation, its role in autophagy, its function in the Keap1-Nrf2 axis and its role as a signaling hub.…”
Section: Discussionmentioning
confidence: 99%
“…osteosarcoma, oral squamous cell carcinoma, cutaneous malignant melanoma, esophageal adenocarcinoma, ovarian, colon, breast and non-small cell lung cancers, and solid tumors Daniels et al, 2013;Ellis et al, 2014;Giatromanolaki et al, 2014;Inoue et al, 2012;Iwadate et al, 2014;Liu et al, 2014a;Luo et al, 2013;Ma et al, 2018;Niklaus et al, 2017;Park et al, 2013;Ruan et al, 2018;Schläfli et al, 2016), and has attracted attention as a potential therapeutic target (Yan et al, 2017;Zhang et al, 2016). An antitumor SQSTM1 DNA vaccine has already been developed and trialed in humans (Gabai et al, 2014;Ponomarenko et al, 2017;Sabbieti et al, 2015;Venanzi et al, 2013); however, SQSTM1 can have both beneficial and deleterious effects depending on the pathological context, as is the case for autophagy itself (Dikic and Elazar, 2018). Then, any hope to develop successful therapeutic strategies in pathologies with SQSTM1 alterations needs to keep in mind the complexity of the SQSTM1 signaling network and how it is affected in each particular disease situation: its tight posttranslational regulation, its role in autophagy, its function in the Keap1-Nrf2 axis and its role as a signaling hub.…”
Section: Discussionmentioning
confidence: 99%
“…Of note p62 DNA treatment of patients partially restored their sensitivity to conventional chemotherapy which they previously failed . However, it remains to be revealed if the anti‐cancer activity of p62‐encoding plasmid in humans is due to a direct adaptive immune response it elicits against the over‐expressed p62 as it was originally hypothesized or if the anti‐cancer effect results from the fact that the plasmid reduces chronic inflammation as observed in animal models for osteoporosis, age‐related macular degeneration and diet‐induced obesity .…”
Section: Discussionmentioning
confidence: 98%
“…More than 30 clinical studies are reported already testing autophagy inhibitors instead of, or in combinations with other types of cancer therapy . Simultaneously, preclinical studies aim to develop drugs and vaccines targeting p62 to fight cancer …”
Section: Introductionmentioning
confidence: 99%
“…p62 vaccination has been used to suppress tumor metastasis in mice with sarcoma and in dogs with mammary tumors. It also dramatically decreased the number and sizes of lung or lymphatic metastases [45-47]. For improving the treatment of osteosarcoma, p62 vaccine may also be used as a novel cancer therapy for osteosarcoma in the future.…”
Section: Discussionmentioning
confidence: 99%